1342. Comparison of Lysin CF-301 (Exebacase) Activity Against S. aureus Isolates From Bacteremic Patients Enrolled in a Phase 2 Study (CF-301-102) to Contemporary Surveillance Isolates. (26th November 2018) - Anastasiou, Diane; Jandourek, Alena; Traczewski, Maria; Cassino, Cara; Schuch, Raymond
Abstract: Background: CF-301 (exebacase) is a novel, recombinantly produced, bacteriophage-derived lysin (cell wall hydrolase) which is the first lysin to enter Phase 2 (Ph2) in the United States and is being studied for the treatment of S. aureus bacteremia including endocarditis. We examined the activity of CF-301 against methicillin-sensitive and methicillin-resistant S. aureus (MSSA and MRSA) isolates from participants in the ongoing, CF-301 "first in-patient' Ph2 study (NCT03163446) in comparison to activity reported in a recent surveillance study. Methods: Patients with complicated bacteremia or endocarditis caused by S. aureus were enrolled into Study CF-301-102 at study centers in the United States and Guatemala between 2017 and 2018. Baseline isolates from blood cultures were collected prior to administration of CF-301. The activity of CF-301 activity against the first 36 isolates of MRSA (14) and MSSA (22) was determined at a central laboratory. Surveillance data for CF-301 were generated against 300 isolates of MRSA (150) and MSSA (150) collected between 2016 and 2017 from patients with various infection types at US centers. CF-301 MICs were determined using the modified broth microdilution method approved by the CLSI for CF-301. Results: In vitro activity of CF-301 against S. aureus isolates from Ph2 Study CF-301-102 and surveillance Conclusion: The activity of CF-301 against baseline S. aureus isolates from blood cultures obtained from bacteremic patients enrolled in the Ph2 study was similar to that observed in the surveillance study. Based on data from previously presented exposure target attainment animal studies, PK/PD modeling and preliminary non-clinical breakpoint assessments, we expect that strains with MIC values of ≤1 µg/mL will be susceptible to the clinical CF-301 dose (0.25mg/kg) under study in Ph2. Disclosures: D. Anastasiou, ContraFect Corporation: Consultant, Consulting fee. A. Jandourek, ContraFect Corporation: Employee, Salary. C. Cassino, ContraFect Corporation: Employee, Salary. R. Schuch, ContraFect Corporation: Employee, Salary.